Follicular mucinosis. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2004)
Follicular mucinosis is a syndrome deriving from the degeneration of the epithelial cell of the external sheath of the hair root. This process gives rise to cystic cavities, in which mucin accumulates, and finally leads to fall of the hairs. It may be idiopathic or associated to T lymphomas, particularly mycosis fungoides (4, 5, 6). The benign idiopathic form and localization to the head and neck are more frequent in children (2, 3), but cases associated to T lymphomas have been reported (1). The clinical features are not diriment, but the presence of an infiltrated alopecic plaque should rise the suspicion of follicular mucinosis. On the other hand, the histological examination (Fig. 2) is diriment, showing in the dermis Alcian blue positive and PAS negative mucin deposits, besides a lymphocytic infiltrate disarranging the hair follicle. The treatment is directed to the basic disorder, when this is present, whereas in the idopathic form topical and/or systemic corticosteroids are indicated.